Public willingness to pay for an entrance fee at the newly proposed Marine protected area in Malacca - Ahmad Sufi, Ayu Naqibah; Matthew, Nitanan Koshy; Japry, Julia Aqila; Nik Ab Rahim, Nik Nor Rahimah; Ya'Cob, Mohd Rusli; Abdurofi, Ilmas (Malaysian Nature Society, 2024)
Pulau Undan, Pulau Nangka, and Pulau Dodol have been selected to be gazetted as the newly proposed Marine Protected Area (MPA) in Malacca, known as the Malacca Marine Park. However, these islands faced issues such as overfishing and land reclamation. Furthermore, appropriate entrance fee has yet to be determined for the newly proposed marine park. This study aimed to ascertain the public's perception and identify the factors influencing their willingness to pay (WTP) for an entrance fee at newly proposed marine park. The public's WTP was estimated using Contingent Valuation Method (CVM). Questionnaires were used to obtain responses from 405 participants via convenience sampling at the entrance point of the proposed new MPA in Umbai. Findings of this study indicated a generally positive perception of the proposed marine park. The factors influencing WTP include age, income, and perception, with an average willingness to pay of RM14.38 (based on the Double Bound CVM). The Department of Fisheries can benefit from this study to justify the entrance fee and design an effective strategy for maintaining the sustainability of the marine park in alignment with the Sustainable Development Goal (SDG) 13 'Life Below Water'.